Entropy-Modulated Oxide–Metal Catalyst Architectures for Direct Ammonia Protonic Ceramic Fuel Cells - Kim, Dongyeon; Park, Dong Jae; Jeong, Incheol; Oh, Seeun; Kim, Hyeonggeun; Lee, Mincheol; Lee, Sang Won; Lee, Kangyong; Chung, Daehan; Roh, Ki‑Min; Bae, Joongmyeon; Shin, Tae Ho; et al. (Nano-Micro Letters, 2026)
Protonic ceramic fuel cells (PCFCs) operating on NH3 present a promising carbon-free energy pathway, yet their performance is often constrained by limited catalytic activity and degradation of conventional Ni-based anodes. Here, we report a high-entropy perovskite catalyst, Sr2Fe1Mo0.2Mn0.2Cr0.2Cu0.2Ni0.2O6-δ (SFMMCCN), employed as an anode catalyst layer in direct ammonia-fed PCFCs. Upon reduction, SFMMCCN undergoes in situ exsolution of Ni–Fe–Cu alloy nanoparticles within a stable oxide matrix. This architecture provides synergistic enhancement of NH3 adsorption and decomposition through the combined effects of abundant surface acid sites and catalytically active alloy interfaces. As a result, the SFMMCCN cell achieves a record peak power density of 2.04 W cm⁻2 at 700 °C and demonstrates excellent operational stability for over 255 h at 600 °C under NH3 fuel. Compared to a bare cell, it exhibits significantly reduced polarization resistance and effectively suppresses Ni coarsening. Density functional theory calculations reveal that the high-entropy oxide framework, together with the exsolved Ni–Fe–Cu alloy, lowers the energy barriers for NH3 decomposition, thereby accelerating overall catalytic kinetics. These findings highlight entropy-controlled oxide–metal architectures as a powerful strategy to achieve both high performance and durability in NH3-fueled electrochemical systems, offering a viable pathway toward scalable and efficient hydrogen-based power generation. Highlights: 1 Entropy-modulated oxide–metal catalyst exsolving Ni–Fe–Cu alloy nanoparticles from a high-entropy perovskite matrix enables efficient and durable ammonia decomposition. 2 Density functional theory calculations reveal that the high-entropy oxide framework facilitates cation exsolution and lowers the kinetic barriers for NH3 decomposition; additionally, the exsolved Ni–Fe–Cu alloy nanoparticles exhibit markedly higher catalytic activity than single-metal surfaces. 3 Direct ammonia protonic ceramic fuel cells (DA-PCFCs) incorporating the Sr2Fe1Mo0.2Mn0.2Cr0.2Cu0.2Ni0.2O6-δ (SFMMCCN) catalyst layer achieve a record-high power density of 2.04 W cm−2 at 700 °C with stable operation for over 255 h under NH3 fuel, demonstrating the effectiveness of the entropy-modulated catalyst in designing durable and high-performance DA-PCFCs for carbon-free ammonia-to-power technologies.